2016
DOI: 10.1038/srep31119
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap formation is increased in psoriasis and induces human β-defensin-2 production in epidermal keratinocytes

Abstract: Neutrophil extracellular traps (NETs) have been implicated in the development of certain immune-mediated diseases, but their role in psoriasis has not been clearly defined. Human β-defensin-2 (HBD-2) is an important antimicrobial peptide overexpressed in psoriasis epidermis. We evaluated whether the amount of NETs is increased in psoriasis and determined the effect of NETs on HBD-2 production in epidermal keratinocytes. Using fluorescent microscopy, we found that patients with psoriasis (n = 48) had higher amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 63 publications
8
153
0
7
Order By: Relevance
“…Being able to discriminate between NETs derived through NOX-dependent or NOX-independent pathways, we next assessed whether we could detect NOX-dependent or NOX-independent NETs in blood plasma obtained from patients with prototype NET-associated diseases; that is, septic shock,28 RA,13 psoriatic arthritis (PsA)29 and SLE 30. We first measured circulating MPO–DNA complexes and then evaluated whether positivity in the MPO–DNA ELISA coincided with positivity in additional ELISAs employing anti-histone antibodies directed against N-terminal tails (H2B-K12Ac and/or H4-K8,12,16Ac).…”
Section: Resultsmentioning
confidence: 99%
“…Being able to discriminate between NETs derived through NOX-dependent or NOX-independent pathways, we next assessed whether we could detect NOX-dependent or NOX-independent NETs in blood plasma obtained from patients with prototype NET-associated diseases; that is, septic shock,28 RA,13 psoriatic arthritis (PsA)29 and SLE 30. We first measured circulating MPO–DNA complexes and then evaluated whether positivity in the MPO–DNA ELISA coincided with positivity in additional ELISAs employing anti-histone antibodies directed against N-terminal tails (H2B-K12Ac and/or H4-K8,12,16Ac).…”
Section: Resultsmentioning
confidence: 99%
“…They also contain granules and can release anti-microbial molecules similar to the resident granulocytes and can create “neutrophil extracellular traps” (NETs). NETs are networks of DNA-rich fibers embedded with histones and granule proteins including neutrophil elastase, cathepsin G and myeloperoxidase that can trap and kill bacteria and fungi extracellularly, without phagocytosis (40, 45, 93, 107). The monocytes can differentiate into macrophages when they enter the tissue and also phagocytose cells and debris.…”
Section: What Is Inflammation?mentioning
confidence: 99%
“…Despite these findings, murine RA models using PAD4 (enzyme driving protein citrullination in neutrophils) knock-out mice to interrogate NET contribution in vivo, revealed discrepant results depending on the arthritis model used and relative contributions of different PADs in the microenvironmental RA context. 7,51,84 Among dermatologic indications, neutrophilic inflammation and NETosis have attracted particular attention for psoriasis 85,86 where neutrophils are found as major infiltrating immune cell in skin histologies, yet their functional relevance in disease initiation or progression remains largely elusive. A previous publication showed that the nucleic acid sensor AIM2 is involved in the uptake of DNA into keratinocytes if the DNA is complexed with LL-37.…”
Section: Featuring Neutrophil Extracellular Trap Formationmentioning
confidence: 99%